2007
DOI: 10.1093/jnci/djm086
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Thromboembolic Events in Patients with Metastatic Carcinoma Treated with Chemotherapy and Bevacizumab

Abstract: Combination treatment with bevacizumab and chemotherapy, compared with chemotherapy alone, was associated with an increased risk of arterial thromboembolism but not venous thromboembolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
510
4
18

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 874 publications
(543 citation statements)
references
References 16 publications
11
510
4
18
Order By: Relevance
“…However, after three cycles of treatment, PCT and PLT values were higher in patients receiving Bevacizumab, which has been reported to be associated with delayed wound healing, gastrointestinal perforation, hemorrahage, venous and arterial thromboembolism, hypertension and proteinuria (Gordon et al, 2005). In addition, arterial thrombosis has been observed to be increased in patients with metastatic colon cancer using Bevacizumab (Scappaticci et al, 2007). Similarly, our study showed a higher incidence of thrombosis in patients receiving Bevacizumab (7 vs 4 pts) (p=0.07).…”
Section: Discussionmentioning
confidence: 99%
“…However, after three cycles of treatment, PCT and PLT values were higher in patients receiving Bevacizumab, which has been reported to be associated with delayed wound healing, gastrointestinal perforation, hemorrahage, venous and arterial thromboembolism, hypertension and proteinuria (Gordon et al, 2005). In addition, arterial thrombosis has been observed to be increased in patients with metastatic colon cancer using Bevacizumab (Scappaticci et al, 2007). Similarly, our study showed a higher incidence of thrombosis in patients receiving Bevacizumab (7 vs 4 pts) (p=0.07).…”
Section: Discussionmentioning
confidence: 99%
“…Several adverse events have been reported with the systemic administration of anti-VEGF monoclonal antibodies, including thromboembolic events, myocardial infarction, stroke, hypertension, gastrointestinal perforations, and kidney disease. 25,[41][42][43] As all of the intravitreal anti-VEGF agents have been reported to be associated with detectable levels in the systemic circulation that may significantly suppress systemic VEGF levels, there is a scientific rationale for the occurrence of potential systemic adverse events. 43 Large-scale clinical trials have demonstrated that pegaptanib has an excellent safety profile, with no systemic adverse effects attributable to VEGF inhibition.…”
Section: Methodsmentioning
confidence: 99%
“…The use of bevacizumab was associated with a 3.1% risk for severe bleeding (versus 2.5% for placebo) and a 1.5% rate of gastrointestinal perforation (versus none for placebo). Other grade Ն3 toxicities attributed to bevacizumab included arterial thromboembolic events (2% versus 1%), wound-healing complications (1.3% versus 0.5), and proteinuria (any proteinuria, 26% versus 21%, but no difference in grade 2 or 3 proteinuria) [1,65,66]. The incidence rates of adverse events were similar in the NO16966 clinical trial (Table 4 and Fig.…”
Section: Toxicitymentioning
confidence: 95%